2017
DOI: 10.1136/bjsports-2016-097419
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms associated with the risk of concussion in 1056 college athletes: a multicentre prospective cohort study

Abstract: CC was associated with a three times greater concussion risk and 4 with a 40% lower risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…One study by Terrell et al sought to explore the effect of the Asp385Ala SNP on outcome after SRC. After evaluating 1056 collegiate athletes, 133 of which suffered a SRC, the authors concluded that the Asp385Ala SNP increased risk of SRC compared to the population without this SNP [59]. These findings begin to demonstrate the complex biomolecular underpinnings of concussion and recovery and warrant further exploration.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study by Terrell et al sought to explore the effect of the Asp385Ala SNP on outcome after SRC. After evaluating 1056 collegiate athletes, 133 of which suffered a SRC, the authors concluded that the Asp385Ala SNP increased risk of SRC compared to the population without this SNP [59]. These findings begin to demonstrate the complex biomolecular underpinnings of concussion and recovery and warrant further exploration.…”
Section: Future Directionsmentioning
confidence: 99%
“…This could support a theory that the lipid transport and neuromodulation after concussion in the pediatric population is different from that of adults. Another study found that having the APOE e4 allele decreased the risk of suffering a concussion in college athletes by up to 40% [59]. With the incongruities of reported data on APOE e4 concussion risk, outcome, and symptom severity, future studies should aim to investigate each of these variables in the same or more similar populations [64].…”
Section: Future Directionsmentioning
confidence: 99%
“…Terrell et al [2] reported a nonsignificant observation that the MAPT rs10445337 TT genotype was weakly associated with a history of one or more concussions (odds ratio, 2.1; 95% CI, 0.3 to 14.5). Similarly, in a later study, no association was observed between concussion incidence and MAPT rs10445337 [22]. Recently, other MAPT SNPs (rs2435211 and rs2435200) have been implicated as potential pathophysiological mechanisms in RU players [20].…”
Section: Microtubule-associated Protein Tau Polymorphismsmentioning
confidence: 84%
“…However, a further step to better understanding inter-individual variability involves genetic variation and its association with concussion and related phenotypes. Evidence already exists suggesting an association between several genetic factors and inter-individual variability in traumatic brain injury incidence and severity [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Dretsch et al reported that soldiers carrying the brain-derived neurotrophic factor ( BDNF ) Met/Met genotype had a higher incidence of mTBI compared to non-Met/Met carriers [12]. In a prospective cohort study, interleukin-6 receptor ( IL-6R ) and apolipoprotein E ( APOE ) variants were significantly associated with the risk of concussion among 1056 college athletes [13]. A relationship between TAU variants and concussion history was also reported in rugby union players [14].…”
Section: Introductionmentioning
confidence: 99%